BUDGET GAMING, SUPERIOR TRUST AND BUDGET EMPHASIS: THE MODERATING EFFECT OF PERSONALITY (Evidence from Retail Company in Indonesia) - Carolina, Yenni; Rapina, R; Amazia, Naftaly Patria; Tanuwinata, Vincent (Riset Akuntansi dan Keuangan Indonesia, 2022)
This research was conducted to obtain empirical evidence on the practice of budgetary gaming. Many researchers say that budgetary gaming is an unethical practice and often occurs in practice. This unethical practice is allegedly influenced by budget emphasis and trust. In this study, the personality factor used, namely greed, will be tested as a moderating factor in the relationship between trust and budget emphasis on budget gaming. This research was conducted on retail companies registered in APRINDO (Indonesian Retail Entrepreneurs Association) with middle management respondents. The amount of data that has been collected and can be processed is 96 data. For data processing, SEM is used with the help of SmartPLS software. The results show that budget emphasis has a positive effect on budgetary gaming. Trust has a negative effect on budgetary gaming, and greed is proven to moderate budget emphasis and trust on budgetary gaming. The implications of this research can be a reference for the business world related to the design and use of a budget that can overcome gaming behaviour on a budget.